Diagnóstico de habilidades blandas y su influencia en el desempeño laboral del personal de emergencia y triage, Hospital Dr. Aníbal González Álava - Mendoza Bravo, Ciro Alexander (2025)
The main objective of this study was to diagnose the soft skills and their influence on the work performance of the emergency and triage staff of the Dr. Aníbal González Álava hospital in the city of Calceta, and to analyse their relationship and propose an improvement plan. A Likert scale survey was used, whose internal consistency was validated using Cronbach's alpha. Cluster analysis made it possible to diagnose and classify staff into homogeneous groups, identifying two groups according to soft skills and three according to job performance, revealing significant disparities. Kruskal-Wallis analysis found a significant relationship between soft skills and job performance, although 64.7% of the variables were not statistically significant. The disparities identified were analysed using the Ishikawa diagram, which facilitated the design of an improvement plan focused on the development of these competencies. The implementation of this plan seeks to correct the deficiencies found. This research concludes that soft skills have a significant influence on staff performance. Therefore, their development will contribute to optimising service quality and improving efficiency in the public administration of the health sector.